An Innovative Laboratory Procedure to Expand Chondrocytes with Reduced Dedifferentiation. (April 2018) - Mao, Yong; Hoffman, Tyler; Wu, Amy; Kohn, Joachim
Objective: In vitro expansion of chondrocytes is required for cartilage tissue engineering and clinical cell-based cartilage repair practices. However, the dedifferentiation of chondrocytes during in vitro expansion continues to be a challenge. This study focuses on identifying a cell culture surface to support chondrocyte expansion with reduced dedifferentiation. Design: A less adhesive culture surface, non–tissue culture treated surface (NTC), was tested for its suitability for culturing chondrocytes. The cell expansion and the expression of chondrocyte markers were monitored for at least 2 passages on NTC in comparison with conventional tissue culture treated polystyrene surface (TCP). The ability of expanded chondrocytes to form cartilage tissues was evaluated using pellet culturing and subcutaneous implantation in nude mice. Results: NTC supported bovine chondrocyte proliferation to a clinically relevant expansion requirement within 2 passages. Chondrocyte phenotypes were better maintained when cultured on NTC than on TCP. In vitro pellet culture studies showed that chondrocytes expanded on NTC expressed a higher level of chondrocyte extracellular matrix. Furthermore, the cells expanded on NTC or TCP were implanted subcutaneously as pellets in nude mice for 6 weeks. The recovered pellets showed cartilage-like tissue formation from cells expanded on NTC but not from the cells expanded on TCP. Conclusions: This study presents an innovative and easy culturing procedure to expand chondrocytes with reduced dedifferentiation. This procedure has potential to be developed to expand chondrocytes in vitro for basic research, tissue engineering, and possibly for clinical applications.